Socialisations alimentaires entre touristes et locaux. Formes et effets des expériences culinaires de la plateforme Eatwith - Laura Arciniegas (Communiquer)
In an increasingly connected and globalized world, tourist itineraries before, during and after travel have evolved towards new ways of experiencing and communicating with local people. In this context, spaces for encounters around food between travelers and locals have arisen, in part thanks to developments in collaborative economy and technological advances. Using an ethnographic approach based on the theoretical framework of the sociology of the eater, we have identified four communicative paths about food, showing how each local host, through his or her initiative and creativity, manages to communicate his or her own vision of authenticity. By diverting and reconciling ordinary local life with their vision of cultural authenticity and exclusivity, guests are able to create a new discourse on commensality, food relations and their identity as travelers.